2017
DOI: 10.1038/srep41756
|View full text |Cite
|
Sign up to set email alerts
|

Young Bone-Marrow Sca-1+ Stem Cells Rejuvenate the Aged Heart and Improve Function after Injury through PDGFRβ-Akt pathway

Abstract: Bone marrow (BM) reconstitution with young BM cells in aged recipients restores the functionality of cardiac resident BM-derived progenitors. This study investigated the cell type primarily responsible for this effect. We reconstituted old mice with BM cells from young or old mice and found that the number of stem cell antigen 1 (Sca-1) cells homing to the heart was significantly greater in young than old chimeras. We then reconstituted old mice with young BM Sca-1+ or Sca-1− cells. We found that Sca-1 cells r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Furthermore, we demonstrated that the young BM cells from the reconstituted BM stably integrated in the aged myocardium prior to injury and were required for functional recovery after injury . Subsequently, we identified the stem cell antigen 1 (Sca‐1 + ) cell as the young BM cell type which had the greatest ability to home to the myocardium and protect the aged recipient mouse heart . Sca‐1 has been widely used as a marker to isolate haematopoietic stem cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we demonstrated that the young BM cells from the reconstituted BM stably integrated in the aged myocardium prior to injury and were required for functional recovery after injury . Subsequently, we identified the stem cell antigen 1 (Sca‐1 + ) cell as the young BM cell type which had the greatest ability to home to the myocardium and protect the aged recipient mouse heart . Sca‐1 has been widely used as a marker to isolate haematopoietic stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…15 Subsequently, we identified the stem cell antigen 1 (Sca-1 + ) cell as the young BM cell type which had the greatest ability to home to the myocardium and protect the aged recipient mouse heart. 16 Sca-1 has been widely used as a marker to isolate haematopoietic stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the extent to which inflammatory cell age affects myogenesis in old muscle, we used heterochronic bone marrow transplant. Sca-1 + enriched bone marrow (BM) cells from young or old GFP + donor mice were transplanted into lethally irradiated aged recipients as previously described 20 . Three months after BM transplant, hindlimb muscle was collected for comprehensive flow cytometry, gene expression and locomotive analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This minority cardiac cell population elicited its effects through paracrine‐directed improvement in survival, proliferation, and neovascularization. Subsequently, we found that stem cell antigen 1 (Sca‐1) cells were the key BM cell type involved in the rejuvenation of the aged heart (Li et al, ). We isolated Sca‐1 + or Sca‐1 − cells from the BM of young donor mice and infused them into lethally irradiated old recipients to generate Sca‐1 + or Sca‐1 − chimeras, respectively.…”
Section: Introductionmentioning
confidence: 99%